Development, Satisfaction and Usability of a mobile platform for monitoring the mental health of university students (Research, Society and Development, 2022)
Objective: This study aimed to develop and assess usability and satisfaction a smartphone application (App) that facilitates the screening and monitoring of emotional symptoms and factors associated with mental health in college students. Methodology: This is a cross-sectional study, with the application of questionnaires using Google Forms® among medical students at a University Center, between July 2020 and November 2021. After using the App developed by a multidisciplinary team, the students responded clinical-demographic data, a Portuguese version of the system usability scale (SUS-System Usability Scale) and a questionnaire on satisfaction with the application. Results: The App, available for Android and iOS platforms, contained 32 self-applicable questions from scales validated in Brazil on depression, anxiety, stress, insomnia and sedentary lifestyle (Depression, Anxiety and Stress Scale -DASS-21, Insomnia Severity Index -ISI and International Physical Activity Questionnaire -IPAQ). At the end of the responses, interpretations were provided based on the scores obtained, including guidance on when to seek professional help and educational content. 31 students answered the usability and satisfaction questionnaires after testing the App. The average age was 25.2 years. 16.1% had a previous or current diagnosis of depressive disorder, and 41.9% of anxiety. The mean score on the SUS scale was 84. All students were satisfied with the application and would recommend it to another classmate. Conclusion: There was good usability and satisfaction, suggesting potential for screening and monitoring the App for mental disorders among medical students.